2015
DOI: 10.1007/s10802-015-0044-5
|View full text |Cite
|
Sign up to set email alerts
|

Linking Executive Function and Peer Problems from Early Childhood Through Middle Adolescence

Abstract: Peer interactions and executive function play central roles in the development of healthy children, as peer problems have been indicative of lower cognitive competencies such as self-regulatory behavior and poor executive function has been indicative of problem behaviors and social dysfunction. However, few studies have focused on the relation between peer interactions and executive function and the underlying mechanisms that may create this link. Using a national sample (n = 1,164, 48.6% female) from the Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
136
6
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(168 citation statements)
references
References 65 publications
11
136
6
8
Order By: Relevance
“…Specifically, working memory abilities were associated with ADHD-related heterogeneity in all three functional domains, processing speed predicted teacher-reported social functioning, and inhibitory control predicted caregiver perceptions of family functioning. These findings were generally consistent with the developmental literature (Holmes et al, 2016) and previous comparisons of ADHD and typically developing groups (Chhabildas et al, 2001; Rapport et al, 2013; Rucklidge & Tannock, 2002), and extend previous findings by demonstrating that specific neurocognitive abilities are important for understanding heterogeneity in functional impairments among children with ADHD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Specifically, working memory abilities were associated with ADHD-related heterogeneity in all three functional domains, processing speed predicted teacher-reported social functioning, and inhibitory control predicted caregiver perceptions of family functioning. These findings were generally consistent with the developmental literature (Holmes et al, 2016) and previous comparisons of ADHD and typically developing groups (Chhabildas et al, 2001; Rapport et al, 2013; Rucklidge & Tannock, 2002), and extend previous findings by demonstrating that specific neurocognitive abilities are important for understanding heterogeneity in functional impairments among children with ADHD.…”
Section: Discussionsupporting
confidence: 90%
“…First, the neurocognitive functions implicated in ADHD have been linked developmentally with a wide array of academic (Barry, Lyman, & Klinger, 2002; Thorell, 2007) and social/peer outcomes (Clark, Prior, & Kinsella, 2002; Dennis, Brotman, Huang, & Gouley, 2007; Holmes, Kim-Spoon, & Deater-Deckard, 2016). For example, developmental research suggests strong links between children’s working memory abilities and their social (Alloway et al, 2005) and academic functioning (Thorell, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study demonstrated that earlier EF (measured by behavioral performance) was associated with later externalizing symptomatology (controlling for the autoregressive effects of earlier externalizing symptomatology) spanning early childhood through middle childhood in a community sample (Sulik al., 2015). In a longitudinal community sample spanning middle childhood through middle adolescence, better EF (measured by behavioral performance) reduced the likelihood of experiencing problems in peer relationships later on (Holmes, Kim-Spoon, & Deater-Deckard, 2016). Finally, there is evidence that adolescents with greater neural activation during an EF task that taxes cognitive/attention network exhibited decreases in social competence over time, particularly in chaotic home environments (Kim-Spoon, Maciejewski, Lee, Deater-Deckard, & King-Casas, 2017).…”
mentioning
confidence: 99%
“…These functions work together to guide goal-directed behaviors and are predictive of a number of social (Holmes, Kim-Spoon, & Deater-Deckard, 2016), academic (Becker, Miao, Duncan, & McClelland, 2014), and psychological (Letkiewicz et al, 2014; Li, 2015) outcomes. Research has demonstrated that individual differences in EF emerge throughout childhood and adolescence as a function of genetic and environmental conditions, and that EF is transmitted across generations such that strengths or deficiencies in parent EF are similarly manifested in the child (Deater-Deckard, 2014).…”
mentioning
confidence: 99%